Co-based organic coordination nanoparticles, preparation method thereof, photoresist composition and application thereof

Through the combination of Co-based organic coordination nanoparticles with photoinitiators and solvents, high-efficiency photoresist is formed, which solves the problems of large edge roughness and low resolution of traditional photoresist patterns, and achieves high resolution and low line roughness lithographic performance.

CN119241603AActive Publication Date: 2025-01-03HUARUI CORE MATERIAL (WUXI) TECH CO LTD

Patent Information

Application Number
CN202310769734.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2025-01-03
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

Traditional photoresist has problems with large roughness in the edges of the graphics and low graphics resolution, especially Co-based nano-organic ligand photoresist, which has not been reported, which has affected the performance of the photoresist.

Method used

Co2(C7H7COO)4(CH3C2N2H3)2 nanoparticles were prepared by specific synthetic methods using Co-based organic coordination nanoparticles, and combined with photoinitiators and organic dispersion solvents to form a photoresist composition, using spin coating. In this way, a photolithographic pattern is formed on the substrate, and the development is achieved through electron beam or ultraviolet light exposure.

Benefits of technology

The lithographic performance of high resolution, high sensitivity and low line roughness is achieved, and the etching effect of the photoresist is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241603A_ABST
    Figure CN119241603A_ABST
Patent Text Reader

Abstract

The invention relates to a Co-based organic coordination nanoparticle, a preparation method thereof, a photoresist composition and application thereof. The Co-based organic coordination nanoparticles provided by the invention have a general formula of ComRnQxMyNz, and Co is two kinds of ions of divalent Co and trivalent Co; r is selected from benzoic acid group or m-methyl benzoic acid group; q can be selected from imidazole and derivatives thereof; m is carboxylic acid; n is crystal water, and the size of the Co-based organic coordination nanoparticle crystal is 1nm-5nm. The nano-particles are prepared into the photoresist composition, exposure and development are carried out through electron beams or medium ultraviolet light, deep ultraviolet light and extreme ultraviolet light, patterns with high resolution, high sensitivity and low line roughness can be obtained, and the Co-based organic coordination nano-particles and the photoresist composition thereof have good application potential in the field of EUV photoetching.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoresists, and in particular to Co-based organic coordination nanoparticles and a preparation method thereof, a photoresist composition and an application thereof. Background Art

[0002] Photoresist refers to a corrosion-resistant thin film material whose solubility changes when exposed to ultraviolet light, electron beam, particle beam, extreme ultraviolet (EUV) or soft x-rays. With the continuous advancement of semiconductor technology and the development of Moore's Law, semiconductor processes have continued to shrink, and higher requirements have been placed on the reduction of processing feature sizes. In order to meet more advanced semiconductor processes and achieve smaller feature sizes, photolithography technology is also constantly developing, from I-line, G-line, deep ultraviolet (DUV), 193nm, immersion 193nm to extreme ultraviolet lithography, electron beam lithography and other fine processing methods. After the photoresist film is exposed and developed to form a photolithographic pattern, it will be dry or wet etched. The part of the substrate material not covered by the film is directly etched, while the substrate surface covered by the film is protected by the photoresist film and is not etched. Etching resistance is a very important evaluation index of photoresist. Excellent etching resistance can ensure that the photoresist can protect the substrate surface from damage during the etching process, effectively simplify the etching process, and greatly improve the yield of the finished etching product.

[0003] Traditional photoresists have complex components, including photoresist resin, photosensitive agent, leveling agent, stabilizer, dispersant, thickener and solvent, etc. The production process is cumbersome and the control process requirements for the ratio and purity are extremely high. Since traditional photoresists are mostly macromolecular polymers and contain many functional additives, their complex components lead to a wide distribution of photoresist sizes, with components of various sizes, and some size conformations can reach 10nm to 20nm, making the size of photoresist patterns difficult to control and may produce many defects. In addition, for traditional photoresists, their scope of use is greatly affected by the wavelength of the light source, and different photoresists are required to match different light sources. At present, metal oxide photoresists have become a research hotspot, and metal oxide photoresists have become a feasible choice for EUV or electron beam exposure of extremely fine patterns. Zn-based nano-organic ligand photoresists are metal oxide organic ligand systems studied by the applicant in the early stage, and their photolithography effects have also been verified in practice. Co and Zn are close in position in the periodic table and have similar properties, so they have the potential to be used as photoresists. However, there are no reports on Co-based nano-organic ligand photoresists. The present invention conducts in-depth research on this material system and synthesizes a Co-based nano-organic photoresist composition with good lithography effect. Summary of the invention

[0004] Aiming at the problem that the pattern edge roughness obtained by conventional photoresist lithography is large and the pattern resolution is low, the present invention provides a novel Co-based organic coordination nanoparticle and a preparation method thereof, a photoresist composition containing the same and application thereof.

[0005]

Prepared metal organic nanoparticles

[0006] The present invention provides a Co-based organic coordination nanoparticle, the general formula of which is: Co m R n Q x M y N z ,in,

[0007] Co is two ions, divalent Co and trivalent Co; m, n, and x are all greater than 0, and y and z are greater than or equal to 0;

[0008] R can be selected from

[0009] Q may be selected from imidazole and its derivatives;

[0010] M is a carboxylic acid;

[0011] N is crystal water;

[0012] Furthermore, the size of the Co-based organic coordination nanoparticle crystal is 1nm-5nm.

[0013] Furthermore, the Co-based organic coordination nanoparticles may have the following structure:

[0014] Co 12 (C6H5COO) 12 (CH3C2N2H3) 12 (CH3COO) 18 (H2O)6 or

[0015] Co2(C7H7COO)4(CH3C2N2H3)2.

[0016]

Method for preparing metal-organic coordination nanoparticles

[0017] Co2(C7H7COO)4(CH3C2N2H3)2 nanoparticles were prepared by the following method:

[0018] Add m-toluic acid or benzoic acid and cobalt acetate into a flask respectively, add an organic solvent to dissolve the m-toluic acid or benzoic acid and cobalt acetate, then add 1-methylimidazole, continue stirring at a certain temperature, and obtain the product by rotary evaporation at a certain steam pressure.

[0019] Furthermore, the molar ratio of the m-toluic acid or benzoic acid to cobalt acetate is in the range of 1:2 to 2:1, and the molar ratio of the m-toluic acid or benzoic acid, cobalt acetate and 1-methylimidazole is in the range of 1:1:(1 to 3).

[0020] The organic solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, tetrahydrofuran, methanol, ethanol, and propanol.

[0021] The stirring temperature is controlled at 25-125°C, preferably 30-100°C, more preferably 30-80°C; the rotary evaporation pressure range is controlled at 70-140mBar, preferably 70-120mBar, more preferably 80-100mBar; at the same time, the rotary evaporation temperature is controlled at 30-45°C, preferably 30-40°C.

[0022]

Metal-organic coordination nanoparticle photoresist

[0023] The invention also provides a photoresist composition, comprising the Co-based organic coordination nanoparticles.

[0024] Furthermore, the above-mentioned photoresist composition further includes a photoinitiator and an organic dispersing solvent, wherein the photoinitiator preferably occupies 0.5wt%-10wt% of the composition, and the nanoparticles preferably occupy 3wt%-20wt% of the composition.

[0025] Further, the photoinitiator is selected from any one or more of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, 1,4-aminonaphthalenesulfonic acid, 2-amino-5,7-naphthalene disulfonic acid, tert-butylphenyl iodonium salt perfluorooctanesulfonic acid, triphenylsulfonium perfluorobutanesulfonic acid, triphenylsulfonium perfluorobutyl and triphenylsulfonium trifluorosulfonic acid.

[0026] Furthermore, the organic dispersing solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, methanol, ethanol, and propanol. The solvent is preferably ethyl acetate.

[0027]

Method for patterning metal-organic coordination nanoparticles in photoresist

[0028] The present invention also provides a method for forming a photolithographic pattern, using the above-mentioned photoresist composition, dripping the photoresist composition onto a substrate by spin coating, heating it on a hot stage, then exposing it with an electron beam or mid-ultraviolet, deep ultraviolet, or extreme ultraviolet, and developing it with a developer.

[0029] The spin coating speed is further controlled at 1500-2500 rpm; the heating temperature of the hot stage is controlled at 50-80° C., and the heating time is controlled at 40-120 s.

[0030] Furthermore, the exposure dose is 50 mJ / cm 2 ~500mJ / cm 2 The preferred exposure dose is 150 mJ / cm 2 ~300mJ / cm 2 .

[0031] Furthermore, the developing time may be selected to be 3-10s, preferably 3s, 5s, or 7s.

[0032] Furthermore, the developer is selected from a mixture of any one or more of decahydronaphthalene, tetrahydronaphthalene, indene, indane, quinoline, 1-methylnaphthalene, toluene, o-xylene, m-xylene, ethyl acetate, butyl acetate, ethanol, n-propanol, isopropanol, n-butanol, n-hexane and cyclohexane, and the developing temperature is room temperature or 20°C to 50°C.

[0033] The thickness of the pre-film layer after removing the organic dispersion solvent may be 10 nm to 100 nm. Specifically, the thickness of the pre-film layer may be 10 nm to 20 nm, 20 nm to 30 nm, 30 nm to 40 nm, 40 nm to 50 nm, 50 nm to 60 nm, 60 nm to 70 nm, 70 nm to 80 nm, 80 nm to 90 nm, 90 nm to 100 nm.

[0034] The substrate is selected from a silicon plate. Other substrates that are insoluble in the developer can also be selected according to actual needs.

[0035] Furthermore, the above nanoparticles are used in the field of photoresists, especially electron beam, mid-ultraviolet, deep ultraviolet, and extreme ultraviolet photoresists. Regarding the mask, deep ultraviolet and longer wavelength light sources are transmissive masks, extreme ultraviolet is a reflective mask, and the electron beam is exposed according to the pattern set by the software.

[0036] The Co-based organic coordination nanoparticles obtained by the present invention have a special structure, and under illumination conditions, can interact with a photoinitiator, change the polarity of the material, and agglomerate, causing the solubility of the Co-based organic coordination nanoparticles to change before and after illumination. Due to these characteristics, the Co-based organic coordination nanoparticles are used as photoresist components, and the solubility of the photosensitive part and the light-shielding part of the photoresist in the developer can be different. The photosensitive part agglomerates in the developer and the solubility is reduced, while the light-shielding part does not agglomerate and dissolves in the developer, so that the non-exposed area can be removed after development to obtain a pattern of a desired shape. The Co-based organic coordination nanoparticles of the present invention are used as photoresist components to achieve more excellent lithography performances such as high resolution, high sensitivity, and low line roughness. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1The DLS particle size test graph of the purple viscous liquid prepared in Example 1 and Example 14 of the present invention, wherein the left curve is the test result of Example 1, and the right curve is the test result of Example 14.

[0038] Figure 2A and Figure 2B The chemical structures of the crystals prepared in Example 1 and Example 14 of the present invention are shown respectively;

[0039] Figure 3 The infrared spectrum test patterns of the crystals prepared in Example 1 and Example 14 of the present invention;

[0040] Figure 4-Figure 15 They are respectively the exposure patterns corresponding to embodiments 2 to 13 of the present invention;

[0041] Figure 16-Figure 27 They are respectively the exposure patterns corresponding to embodiments 15-26 of the present invention;

[0042] Fig.28 This is the exposure pattern of Example 27 of the present invention. DETAILED DESCRIPTION

[0043] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0045] The present invention provides a Co-based organic coordination nanoparticle, the general formula of which is: Co m R n Q x M y N z

[0046] Among them, Co is two kinds of ions: divalent Co and trivalent Co;

[0047] R can be selected from

[0048] Q may be selected from imidazole and its derivatives;

[0049] M is carboxylic acid; N is water of crystallization.

[0050] Furthermore, the size of the Co-based organic coordination nanoparticle crystal is 1nm-5nm.

[0051] m, n, x are all greater than 0, y, z are greater than or equal to 0; further, 2≤m≤12, 4≤n≤12, 2≤x≤12, 0≤y≤18, 0≤z≤6;

[0052] Furthermore, the Co-based organic coordination nanoparticles may have the following structure:

[0053] Co 12 (C6H5OO) 12 (CH3C2N2H3) 12 (CH3COO) 18 (H2O)6;

[0054] Co2(C7H7COO)4(CH3C2N2H3)2.

[0055] The Co-based organic coordination nanoparticles obtained by the present invention have a special structure, and under illumination conditions, can interact with a photoinitiator, change the polarity of the material, and agglomerate, causing the solubility of the Co-based organic coordination nanoparticles to change before and after illumination. Due to these characteristics, the Co-based organic coordination nanoparticles are used as photoresist components, and the solubility of the photosensitive part and the light-shielding part of the photoresist in the developer can be different. The photosensitive part agglomerates in the developer and the solubility is reduced, while the light-shielding part does not agglomerate and dissolves in the developer, so that the non-exposed area can be removed after development to obtain a pattern of a desired shape. The Co-based organic coordination nanoparticles of the present invention are used as photoresist components to achieve more excellent lithography performances such as high resolution, high sensitivity, and low line roughness.

[0056] Among them, Co2(C7H7COO)4(CH3C2N2H3)2 nanoparticles are prepared by the following method:

[0057] Add m-toluic acid or benzoic acid and cobalt acetate into a flask respectively, add an organic solvent to dissolve the m-toluic acid or benzoic acid and cobalt acetate, then add 1-methylimidazole, continue stirring at a certain temperature, and obtain the product by rotary evaporation at a certain steam pressure.

[0058] Further, the molar ratio of the m-toluic acid or benzoic acid to cobalt acetate is in the range of 1:2 to 2:1, and the molar ratio of the m-toluic acid or benzoic acid, cobalt acetate, and 1-methylimidazole is in the range of 1:1:(1 to 3);

[0059] The organic solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, tetrahydrofuran, methanol, ethanol, and propanol.

[0060] The stirring temperature is controlled at 25-125°C, preferably 30-100°C, more preferably 30-80°C; the rotary evaporation pressure range is controlled at 70-140mBar, preferably 70-120mBar, more preferably 80-100mBar; at the same time, the rotary evaporation temperature is controlled at 30-45°C, preferably 30-40°C.

[0061] The present invention also provides a photoresist composition, comprising the above-mentioned Co-based organic coordination nanoparticles. Further, the above-mentioned photoresist composition also includes a photoinitiator and an organic dispersing solvent, wherein the photoinitiator preferably occupies 0.5wt%-10wt% of the composition, and the nanoparticles preferably occupy 3wt%-20wt% of the composition.

[0062] Further, the photoinitiator is selected from any one or more of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, 1,4-aminonaphthalenesulfonic acid, 2-amino-5,7-naphthalene disulfonic acid, tert-butylphenyl iodonium salt perfluorooctanesulfonic acid, triphenylsulfonium perfluorobutanesulfonic acid, triphenylsulfonium perfluorobutyl and triphenylsulfonium trifluorosulfonic acid.

[0063] Furthermore, the organic dispersing solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, methanol, ethanol, and propanol. The solvent is preferably ethyl acetate.

[0064] The present invention also provides a method for forming a photolithographic pattern, using the above-mentioned photoresist composition, dripping the photoresist composition onto a substrate by spin coating, heating it on a hot stage, then exposing it with an electron beam or mid-ultraviolet, deep ultraviolet, or extreme ultraviolet, and developing it with a developer.

[0065] The spin coating speed is further controlled at 1500-2500 rpm; the heating temperature of the hot stage is controlled at 50-80° C., and the heating time is controlled at 40-120 s.

[0066] Furthermore, the exposure dose is 50 mJ / cm 2 ~500mJ / cm 2 The preferred exposure dose is 150 mJ / cm 2 ~300mJ / cm 2 .

[0067] Further, the developing time may be selected to be 3-10s, preferably 3s, 5s, 7s;

[0068] Furthermore, the developer is selected from a mixture of any one or more of decahydronaphthalene, tetrahydronaphthalene, indene, indane, quinoline, 1-methylnaphthalene, toluene, o-xylene, m-xylene, ethyl acetate, butyl acetate, ethanol, n-propanol, isopropanol, n-butanol, n-hexane and cyclohexane, and the developing temperature is room temperature or 20°C to 50°C.

[0069] The thickness of the pre-film layer after removing the organic dispersion solvent may be 10 nm to 100 nm. Specifically, the thickness of the pre-film layer may be 10 nm to 20 nm, 20 nm to 30 nm, 30 nm to 40 nm, 40 nm to 50 nm, 50 nm to 60 nm, 60 nm to 70 nm, 70 nm to 80 nm, 80 nm to 90 nm, 90 nm to 100 nm.

[0070] The substrate is selected from a silicon plate. Other substrates that are insoluble in the developer can also be selected according to actual needs.

[0071] Furthermore, the above nanoparticles are used in the field of photoresists, especially electron beam, mid-ultraviolet, deep ultraviolet, and extreme ultraviolet photoresists. Regarding the mask, deep ultraviolet and longer wavelength light sources are transmissive masks, extreme ultraviolet is a reflective mask, and the electron beam is exposed according to the pattern set by the software.

[0072] Example 1

[0073] 4.88g (40mmol) benzoic acid and 4.98g (20mmol) cobalt acetate were added to a 100mL flask, and 45mL tetrahydrofuran was added. 1.67-2.30g (20-28mmol) 1-methylimidazole was added and stirred and heated at 25-125°C for 24 hours. The product was rotary evaporated at 70-140mBar and 30-45°C for 20-40 minutes to obtain a purple viscous liquid. The DLS particle size test of the obtained product was as follows: Figure 1 As shown in the left curve, it can be seen that the prepared system is nanoparticles (average particle size 3.1nm). Further, the liquid can be left standing at low temperature to obtain crystals, and infrared spectrum test is performed on it, and the following is obtained: Figure 3 The test results shown in the figure show that at 3130cm -1 There is an absorption peak, which is the absorption peak of the aromatic ring after bonding, because the infrared absorption peak of free benzoic acid is located at 3000-3100cm -1 The stretching vibration of the unsaturated =CH of the benzene ring of the benzoic acid group corresponds to that of the synthesized Co-based organic ligand structure, which means that a slight shift in the absorption peak position of benzoic acid occurs in the synthesized Co-based organic ligand structure material, indicating that the benzoic acid group is bonded to the molecular structure of the metal organic compound. 12 (C6H5OO) 12(CH3C2N2H3) 12 (CH3COO) 18 (H2O)6, such as Figure 2A As shown. It is a multi-nuclear complex with benzoic acid, N-methylimidazole and acetate as ligands, containing 12 Co rings. Except for N-methylimidazole, the other ligands are connected around the Co ring in the form of bridges. It can be seen that the substance prepared by the method of this embodiment is a metal organic ligand nanoparticle.

[0074] Embodiment 2-4

[0075] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 1 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 50°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain half-pitch line exposure patterns of 9.04μm, 10.01μm, and 10.62μm, respectively. Figure 4 , 5 、6.

[0076] Embodiment 5-7

[0077] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 1 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 60°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain line exposure patterns with half-pitch of 9.48μm, 9.74μm, and 9.92μm, respectively. Figure 7 , 8 、9.

[0078] Examples 8-10

[0079] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 1 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 70°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2, using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain half-pitch line exposure patterns of 9.48μm, 10.62μm, and 10.62μm, respectively. Fig.10 , 11 、12.

[0080] Examples 11-13

[0081] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 1 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 80°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain half-pitch line exposure patterns of 9.04μm, 10.01μm, and 11.06μm, respectively. Fig.13 , 14 、15.

[0082] Embodiment 14

[0083] 5.44 g (40 mmol) of m-methylbenzoic acid and 4.98 g (20 mmol) of cobalt acetate were added to a 100 mL flask, and 45 mL of tetrahydrofuran was added. 1.67-2.30 g (20-28 mmol) of 1-methylimidazole was added and heated at 25-125°C with stirring for 24 hours. The product was rotary evaporated at 70-140 mBar and 30-45°C for 20-40 minutes to obtain a purple viscous liquid. The product was subjected to DLS particle size test, and the results were as follows: Figure 1 As shown in the right curve, it can be seen that the prepared system is nanoparticles (average particle size 4.3nm). Further, the liquid can be left to stand at low temperature to obtain crystals, and infrared spectrum test is performed on it, and the following is obtained: Figure 3 The test results shown in the figure show that at 2922cm -1 、3130cm -1 All of them have an absorption peak. The free m-toluic acid has an absorption peak at 3000-3100 cm -1 There is a stretching vibration absorption peak corresponding to the unsaturated =CH of the benzene ring of the benzoic acid group at 3000cm -1 There will be an additional alkyl CH peak below, and the infrared absorption spectrum of the product prepared in this example also has corresponding absorption peaks near these two positions, and a slight shift has occurred, which indicates that the m-toluic acid group is bonded to the molecular structure of the metal organic compound. The substance prepared by the method of this example is a metal organic ligand nanoparticle. The molecular structure is as follows Figure 2B As shown, Co2(C7H7COO)4(CH3C2N2H3)2.

[0084] Examples 15-17

[0085] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 14 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 50°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain a half-pitch 1μm line exposure pattern, respectively. Fig.16 , 17 、18.

[0086] Examples 18-20

[0087] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 14 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 60°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain a half-pitch 1μm line exposure pattern, respectively. Fig.19 , 20 ,twenty one.

[0088] Examples 21-23

[0089] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 14 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 70°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain a half-pitch 1μm line exposure pattern, respectively. Fig. 22 , 23 ,twenty four.

[0090] Examples 24-26

[0091] 0.5 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 14 (5.0 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto a silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 80°C for 1 minute. The photoresist film was exposed to a 254 nm ultraviolet mercury lamp at a dose of 150 mJ / cm 2 , using mesitylene as developer, developing for 3s, 5s, and 7s respectively, to obtain a half-pitch 1μm line exposure pattern, respectively. Fig.25 , 26 、27.

[0092] Embodiment 27

[0093] 10 wt% PAG-1 (N-hydroxynaphthalimide trifluoromethanesulfonate) was added to the solution prepared in Example 14 (3.5 wt%), the solvent was propylene glycol monoethyl ether acetate, and the solution was spin-coated onto the silicon wafer at a speed of 2000 rpm, and then heated on a hot plate at 60°C for 1 minute. EBL exposure was performed with a dose of 850 μC / cm 2 , beam intensity 1.0~3.0A, mesitylene as developer, development time 9s, half-pitch 100nm line is obtained, see Fig.28 .

[0094] In summary, the present invention obtains a variety of effective nanoparticles and corresponding compositions, verifies the structure and has good lithography performance under mid-ultraviolet and electron beam lithography (EBL) conditions, which can achieve better lithography performance such as high resolution, high sensitivity, and low line roughness.

Claims

1. A Co-based organic coordination nanoparticle, characterized in that: The general formula is: Co m R n Q x M y N z , where Co is two ions, divalent Co and trivalent Co; m, n, x are all greater than 0, and y and z are greater than or equal to 0; R can be selected from Q can be selected from imidazole and its derivatives; M is a carboxylic acid; N is crystal water; The size of the Co-based organic coordination nanoparticle crystal is 1nm-5nm.

2. The Co-based organic coordination nanoparticles according to claim 1, characterized in that: The nanoparticle structure is Co 12 (C6H5COO) 12 (CH3C2N2H3) 12 (CH3COO) 18 (H2O)6 or Co2(C7H7COO)4(CH3C2N2H3)2.

3. The method for preparing Co-based organic coordination nanoparticles according to claim 1 or 2, characterized in that: The specific steps include: Add m-toluic acid or benzoic acid and cobalt acetate into a flask respectively, add an organic solvent to dissolve the m-toluic acid or benzoic acid and the cobalt acetate, then add 1-methylimidazole, continue stirring at a certain temperature, and rotary evaporate at a certain steam pressure to obtain the product.

4. The method for preparing Co-based organic coordination nanoparticles according to claim 3, characterized in that: The molar ratio of the m-toluic acid or benzoic acid to the cobalt acetate is in the range of 0.5-2, and the molar ratio of the m-toluic acid or benzoic acid:cobalt acetate:1-methylimidazole is in the range of 1:1:(1-3).

5. The method for preparing Co-based organic coordination nanoparticles according to claim 3, characterized in that: The organic solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, tetrahydrofuran, methanol, ethanol, and propanol.

6. The method for preparing Co-based organic coordination nanoparticles according to claim 3, characterized in that: The stirring temperature is controlled at 25-125°C, the rotary evaporation pressure range is controlled at 70-140 mBar, and the rotary evaporation temperature is controlled at 30-45°C.

7. A photoresist composition comprising the Co-based organic coordination nanoparticles as described in claim 1 or 2, a photoinitiator and an organic dispersing solvent, wherein the photoinitiator occupies 0.5wt%-10wt% of the composition, and the nanoparticles occupy 3wt%-20wt% of the composition.

8. The photoresist composition according to claim 7, characterized in that: The photoinitiator is selected from any one or more of N-hydroxynaphthaleneimide trifluoromethanesulfonic acid, 1,4-aminonaphthalenesulfonic acid, 2-amino-5,7-naphthalene disulfonic acid, tert-butylphenyl iodonium salt perfluorooctanesulfonic acid, triphenylsulfonium perfluorobutanesulfonic acid, triphenylsulfonium perfluorobutyl and triphenylsulfonium trifluorosulfonic acid.

9. The photoresist composition according to claim 7, characterized in that: The organic dispersing solvent is selected from any one or more of ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, propylene glycol methyl ether acetate, 1-ethoxy-2-propanol, methanol, ethanol, and propanol.

10. A method for forming a photolithographic pattern, characterized in that The photoresist composition according to any one of claims 7 to 9 is added dropwise onto a substrate by spin coating, and heated on a hot stage, and then exposed to electron beam or mid-ultraviolet, deep ultraviolet, or extreme ultraviolet light, and developed with a developer, with a spin coating speed of 1500 to 2500 rpm; the heating temperature of the hot stage is controlled at 50 to 80° C., the heating time is controlled at 40 to 120 s, and the exposure dose is 50 mJ / cm 2 ~500mJ / cm 2 , development time 3-10s.

11. The method for forming a photolithography pattern according to claim 10, characterized in that: The developer is selected from any one or more mixtures of decahydronaphthalene, tetrahydronaphthalene, indene, indane, quinoline, 1-methylnaphthalene, toluene, o-xylene, m-xylene, ethyl acetate, butyl acetate, ethanol, n-propanol, isopropanol, n-butanol, n-hexane and cyclohexane, and the developing temperature is room temperature or 20°C to 50°C.

12. The method for forming a photolithography pattern according to claim 10, characterized in that: The thickness of the pre-film layer after removing the organic dispersion solvent may be 10 nm to 100 nm.

13. The use of the Co-based organic coordination nanoparticles according to claim 1 or 2 is mainly used for electron beam, mid-ultraviolet, deep ultraviolet or extreme ultraviolet photoresist.

Citation Information

Patent Citations

  • Zinc-based metal organic nanoparticles, preparation method thereof and photoresist

    CN114675488A

  • Application of zinc-oxygen cluster compound in field of photoresist

    CN115407607A

  • Organically modified metal oxide nanoparticle, method for producing the same, EUV photoresist material, and method for producing etching mask

    US20210149299A1

  • Organically modified metal oxide nanoparticles, organically modified metal oxide nanoparticles-containing solution, organically modified metal oxide nanoparticles-containing resist composition, and resist pattern forming method

    US20210191261A1

Cited By

  • Method for improving smoothness of micro-nano structure through photoresist pretreatment process

    CN121115410A